Brain Function and Health, Sports, and Exercise - Clemente, Filipe Manuel; Silva, Ana Filipa (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint represents the articles published in the Special Issue "Brain Function and Health, Sports, and Exercise". Fifteen articles were published, with topics covering the relationship between acute effects of exercise on cognitive function, as well as the influence of exercise on positive medium-term adaptations in populations as children, youth, adults and older. We think that the different approaches used in the different articles will help the readers to have a greater overview of the current research in brain and exercise.